Removal of reactive azo dye in a sequencing batch reactor effects of total cycle time and anaerobic retention time ratio - Vu Minh Trang (March 2009)
Towards improving treatment of textile wastewater in a Sequencing batch Reactor (SBR), enriched sludge was used and the react phase involved four phases: (I) first aerobic, (II) first anaerobic, (III) second aerobic, and (IV) second anaerobic. In theis study the effect of total cycle and aerobic: anaerobic time ration on the color removal of wastewater containing azo dye C.I. Reactive Red 141 were determined.
The SBR reactor used a sludge that was taken directly from the Textile and garment Industry zone, Pho Noi province, Vietnam. The sludge was enriched with microorganisms, isolated from an aerobic reactor treating textile waste water in Vietnam. The SBR was fed with synthetic wastewater that contained 100 mg/L of C.I. Reactive Red 141, 1000 mg/L of COD and 4.5 g/L NaHCO3. The time for first anaerobic:first aerobic: second anaerobic: second aerobic phase was varied (Case A) 4.5 h: 6 h: 6 h: 6h; (Case B) 4.5 h: 9h: 6h: 3h and (Case C) 2.5 h: 9 h: 6 h: 5h. The best ratio was 4.5 h: 9h: 6 h: 3h (Case B), in which 85% color was achieved. With an ultimate goal of identifying the by-products azo dye decolorization, this study also showed that the azo bonds were broken but the by-products were not stable and still had aromatic compounds, as well.
Thesis (M.S. in Environmental Engineering)--University of the Philippines Diliman
Keywords: Sewage -- Purification -- Organic compounds removal